Methane emission offsets carbon dioxide uptake in a small productive lake. Issue 6 (10th June 2020) - Vachon, Dominic; Langenegger, Timon; Donis, Daphne; Beaubien, Stan E.; McGinnis, Daniel F.
Abstract: Here, we investigate the importance of net CH4 production and emissions in the carbon (C) budget of a small productive lake by monitoring CH4, CO2, and O2 for two consecutive years. During the study period, the lake was mostly a net emitter of both CH4 and CO2, while showing positive net ecosystem production. The analyses suggest that during the whole study period, 32% ± 26% of C produced by net ecosystem production was ultimately converted to CH4 and emitted to the atmosphere. When converted to global warming potential, CH4 emission (in CO2 equivalents) was about 3–10 times higher than CO2 removal from in‐lake net ecosystem production over 100‐yr and 20‐yr time frames, respectively. Although more work in similar systems is needed to generalize these findings, our results provide evidence of the important greenhouse gas imbalance in human‐impacted aquatic systems.